2021
DOI: 10.30658/jicrcr.4.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Messages in Conflict: Examining Leadership Communication during the COVID-19 Pandemic in the U.S.

Abstract: One year into the COVID-19 pandemic, the U.S. had lost over a half million lives to the virus. Organizations had to shift the way they operated, requiring effective communication to help employees transition. This study examines two important time periods during the pandemic: early May, just after stay-at-home orders began to be lifted, and late November, as infection rates soared. This study quantitatively examines the role of perceived severity, organizational trust, reputation, and credibility on participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Even in states with generally high public compliance to COVID‐19 protective measures, such as Washington, some individuals and communities may be less compliant or trusting of information provided by the state government. Residents of states with high compliance to COVID‐19 may be less likely to perceive COVID‐19 as a risk and take protective measures when they are less trusting of the state government (Sellnow‐Richmond et al., 2023). In an infodemic, it is recommended to communicate from the bottom‐up, a role school nurses are ideally situated to fulfill (McIntosh et al., 2023; Porat et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Even in states with generally high public compliance to COVID‐19 protective measures, such as Washington, some individuals and communities may be less compliant or trusting of information provided by the state government. Residents of states with high compliance to COVID‐19 may be less likely to perceive COVID‐19 as a risk and take protective measures when they are less trusting of the state government (Sellnow‐Richmond et al., 2023). In an infodemic, it is recommended to communicate from the bottom‐up, a role school nurses are ideally situated to fulfill (McIntosh et al., 2023; Porat et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Trustworthiness (source credibility) can help to enhance the effectiveness of crisis response strategies and protects reputation during a crisis. Sano and Sano (2019) argued that in crisis management, source credibility can be more influenced by trustworthiness. When an organization's crisis response strategy lacks a trustworthy source of information, it will give rise to an infodemic quandary which will pose more damage to its reputation in a crisis situation.…”
Section: Conclusion and Suggestionmentioning
confidence: 99%
“…Trustworthiness is the degree of confidence stakeholders have about the veracity of the message in the crisis response. Source credibility refers to the judgements made by the receivers of the crisis response (message) regarding the extent to which the communicator is believable (Pornpitakpan, 2004;Sellnow-Richmond et al, 2021). Hocevar et al (2017) found that 'source credibility significantly drives how we process risk messages'.…”
Section: Introductionmentioning
confidence: 99%
“…The second dimension, message credibility, refers to the cognitive processing of message content (Rouner, 2008). Within crisis communication, message credibility is recognized as the degree stakeholders trust the information provided during a crisis, the degree they rely on it, and their confidence in its accuracy (Flanagin and Metzger, 2013; Sellnow-Richmond et al ., 2021). Perceptions of sources, such as news sources, may also be affected by stakeholders' trust in news media (Knudsen et al ., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%